How firms survive in European emerging markets: A survey - Eduard Baumöhl; Evžen Kočenda (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We survey the empirical evidence on corporate survival and its determinants in European emerging markets. We demonstrate that (i) institutional quality is a significant preventive factor for firm survival in all sectors of the economy, which holds for small, medium and large firms alike. On the other hand, (ii) the impact of financial performance indicators is lower than one would expect. However, (iii) other firm-level variables play more important roles in firm survival, and the most important preventive factors are the legal form of a limited liability company, the number of large shareholders, and the presence of a foreign owner.
Keywords: D22; G01; G33; G34; P34; 330; firm survival; institutions; financial development; European emerging markets; survival and exit determinants; hazards model